2011
DOI: 10.1073/pnas.1012867108
|View full text |Cite
|
Sign up to set email alerts
|

An aquaporin-4/transient receptor potential vanilloid 4 (AQP4/TRPV4) complex is essential for cell-volume control in astrocytes

Abstract: Regulatory volume decrease (RVD) is a key mechanism for volume control that serves to prevent detrimental swelling in response to hypo-osmotic stress. The molecular basis of RVD is not understood. Here we show that a complex containing aquaporin-4 (AQP4) and transient receptor potential vanilloid 4 (TRPV4) is essential for RVD in astrocytes. Astrocytes from AQP4-KO mice and astrocytes treated with TRPV4 siRNA fail to respond to hypotonic stress by increased intracellular Ca 2+ and RVD. Coimmunoprecipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
345
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 315 publications
(364 citation statements)
references
References 32 publications
18
345
1
Order By: Relevance
“…Its precise mechanism is cell type-dependent but was suggested to require TRPV4 and AQP4 in cortical astrocytes. 6 We found that AQP4-mediated facilitation of Ca 2C influx through TRPV4 channels facilitates M€ uller cell RVD yet this was observed only under conditions that are unlikely to occur in vivo (i.e., »50% reduction in tonicity). In contrast, TRPV4 activation (by agonists or swelling) itself augmented glial swelling through an unknown mechanism that required an increase in [Ca 2C ] i and, possibly, activation of phospholipase A2.…”
mentioning
confidence: 74%
“…Its precise mechanism is cell type-dependent but was suggested to require TRPV4 and AQP4 in cortical astrocytes. 6 We found that AQP4-mediated facilitation of Ca 2C influx through TRPV4 channels facilitates M€ uller cell RVD yet this was observed only under conditions that are unlikely to occur in vivo (i.e., »50% reduction in tonicity). In contrast, TRPV4 activation (by agonists or swelling) itself augmented glial swelling through an unknown mechanism that required an increase in [Ca 2C ] i and, possibly, activation of phospholipase A2.…”
mentioning
confidence: 74%
“…However, immunofluorescence and immunogold electron microscopy evidence suggests that TRPV4 channels-plasma membrane cation channels of the transient receptor potential vanilloid (TRPV) family-are localized in astrocytic endfeet; moreover, 4α-phorbol 12,13-didecanoate (4αPDD), a TRPV4-selective chemical activator, increases [Ca 2+ ] i in cultured cortical astrocytes (11). Also in cultured cortical astrocytes, TRPV4 channels form complexes with aquaporin 4 to regulate cell volume responses to hypoosmotic stress (12). Notably, it has been shown that TRPV4 channels in other preparations are activated by epoxyeicosatrienoic acids (EETs) (13)(14)(15), which have been implicated in NVC (16)(17)(18) and reportedly stimulate Ca 2+ influx in rat cortical astrocytes (19,20).…”
Section: Calcium | Parenchymal Arteriolementioning
confidence: 99%
“…Interestingly, the scenario of volume regulation by AQP5/TRPV4 interaction has recently been expanded for AQP4. As demonstrated in mouse astrocytes, the TRPV4/AQP4 complex plays an important role in the initiation of RVD similar to that of the TRPV4/AQP5 complex in salivary gland cells [25] . In this regard, it would npg not be hard to imagine that AQP3 might also form molecular complexes with other ion channels to mediate sperm RVD.…”
Section: Efficient Sperm Volume Regulation Is a Prerequisite For Normmentioning
confidence: 80%
“…Despite the observation that AQP3 is important for normal sperm RVD during hypotonic exposure [3] and the increasing body of evidence that several members of AQPs (AQP1, 2, 3, 4, and 5) are actively involved in RVD of diverse cell types [22][23][24][25][26] , the molecular mechanisms by which AQPs take part in RVD are hard to explain using the "simple permeability" theory, which considers aquaporins as inert pores that simply increase the osmotic permeability of plasma membranes. Under such a "simple permeability" model, RVD begins with a hypotonic stress-induced water influx, followed by active solute transport that enables osmolyte efflux and provides the driving force for water to exit [27] , and the participation of AQPs in RVD is merely to facilitate the time it takes to reach osmotic equilibrium.…”
Section: Efficient Sperm Volume Regulation Is a Prerequisite For Normmentioning
confidence: 99%
See 1 more Smart Citation